PROBLEMATIKA SERTIFIKASI HAK MILIK ATAS TANAH MELALUI AJUDIKASI PASCA BENCANA TSUNAMI DI KOTA BANDA ACEH - MUSTAKIM MUSTAKIM (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd Yamin2. Chairani Bustami3. Syafnil Gani Tsunami disaster has brought an impact to the community especially in the fild of land in which the owner and the border of the land is unknown, the evidence of ownership in the form of Land certificate either owned by the owner or the one kept in the Office National Land Board has been penished. This normative juridical study with analytical descriptive approach described and analyzed the problems to be presented referring to the existing provisions of legislation.The result of this study showed that the implementation of certification of rights to land had succeeded in providing a guarantee of certainty of rights to some of the communities impacted by the tsunami disaster, but the result is not yet able to meet the target set due to several constraints met in the field. The constraints found in the implementation of certification of rightd to land were the emergence of multiple certificates, improper land area, unclear boundary of land because it is not mentioned in the certificate due to the unlikely condition in the field, and the emergence of the name of the previous owner in the new certificate even though the rights to land has been transferred.Keywords : Certification, Adjudication, Tsunami Disaster